The Concept of Faith in Kierkegaard’s Understanding and a Comparison between Aristotle and Augustine - حەمەئەمین حەسەن ڕیبوار; عەزیز سەعید حەمید (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
Kierkegaard (1813-1856) was a Danish philosopher and theologian. Aristotle (384-322 BC) was a classical Greek philosopher, and Augustine (354-450) was an Amazigh theologian and medieval thinker. Three characters thought in three different times, in three different geographies, and in three different lives. All three have settled around the concept of faith and discussed its importance. Aristotle believed in reason, science, and empiricism, and Augustine believed that one acquires faith through reason and thought. Kierkegaard, on the other hand, is a strong critic of reason and science and a strong believer without linking faith to rationality and science. Thus, Kieckgaard agreed with Augustine in many ways and disagreed with him in several things, but he agreed with Aristotle on the existence of God as the source of existence and disagreed with science on the understanding of man. This study examines the contradictions and similarities between these three philosophers by adopting a comparative method of philosophical criticism, taking into account the concept of faith in the minds of these three philosophers and taking this concept into account in our world. The most important conclusion of this study is that difference is of high value and should be preserved in philosophical and intellectual discussions.